Conjectures on the dynamics of secrecy and the secrets business - Wexler, Mark N. (Journal of business ethics, 1987)
This paper provides an analysis of the dynamics of secrecy and the secrets business. Secrets are defined as bits of information that, for one reason or another, are kept hidden or controlled so as to elude attention, observation or comprehension. Three conceptual lenses — the micro-analytic focusing on self-deception, the social-psychological focusing on self-disclosure, and the macro-analytic focusing on public secrets — are probed. Secrecy at each of the three levels is revealed to be a janusfaced issue providing undeniable benefits to Homo sapiens in their efforts to adapt to a changing world yet also creates undeniable problems. While secrecy provides the occasion for the demonstration of loyalty and intimacy, it also generates the conditions for exclusion and betrayal. The contemporary impulse to create public forums in which all is revealed, in which ‘sunlight’ prevails, is too simple a panacea to those who use the topic of secrecy as an occasion to correct social, political and economic problems.